The Quality of Mackerel Tuna (Auxis thazard) Microbiologically Using Different Ice - Fahrul Fahrul; Syahrul Syahrul; Mutia Kamaruddin (Agrikan: Jurnal Agribisnis Perikanan, 2022)
This research aims to determine the microbiological contents of ice used and its effect on mackerel tuna (Auxis thazard) and to determine the amount of microbiological contents of mackerel tuna (Auxis thazard) kept with different sources of ice. This research was conducted in February - April 2020 by adopting experimental design. The microbiological parameters included Total Plate Count (TPC), Coliform, Escherichia coli, and Salmonella, all of which were carried out in laboratory. The data obtained were presented in form of tables and analyzed descriptively. The results showed that the three ices used for storage did not contain Escherichia coli and Salmonella, but did contain TPC and Coliform. The highest TPC and Coliform contents of the three sources of ice was found in ice A with TPC value at incubation temperatures of 22ºC: 62 colonies / 100mL and 37ºC: 107 colonies / 100mL. The Coliform value on ice A was also the highest, which was too much to count. In addition, the results showed that mackerel tuna kept using three different sources of ice did not contain Coliform, Escherichia coli, and Salmonella. However, fish that had not been kept in ice (0 hours) and fish that had been kept in ice all contained TPC, with the highest TPC content of 1.5 x 103 colonies / 100g found in fish kept in ice B. The results showed that mackerel tuna kept in those three different ices were still safe for consumption after storage of 6 hours.